Spiro-oxindole derivative 5-chloro-4′, 5′-diphenyl-3′-(4-(2-(piperidin-1-yl) ethoxy) benzoyl) spiro[indoline-3, 2′-pyrrolidin]-2-one triggers apoptosis in breast cancer cells via restoration of p53 function. (January 2016) - Saxena, Ruchi; Gupta, Garima; Manohar, Murli; Debnath, Utsab; Popli, Pooja; Prabhakar, Yenamandra S.; Konwar, Rituraj; Kumar, Sandeep; Kumar, Atul; Dwivedi, Anila
Highlights: Spirooxindole compound G613 inhibited the Mdm2–p53 interaction in breast cancer cells. G613 selectively suppressed the growth of breast cancer cells and tumor xenograft. Compound triggers p53-mediated transcription-dependent and -independent apoptosis. Compound promoted the interaction of p53 with bcl2 members causing apoptosis. Abstract: Breast cancer remains a significant health problem due to the involvement of multiple aberrant and redundant signaling pathways in tumorigenesis and the development of resistance to the existing therapeutic agents. Therefore, the search for novel chemotherapeutic agents for effective management of breast cancer is still warranted. In an effort to develop new anti-breast cancer agents, we have synthesized and identified novel spiro-oxindole derivative G613 i.e. 5-chloro-4′, 5′-diphenyl-3′-(4-(2-(piperidin-1-yl) ethoxy) benzoyl) spiro[indoline-3, 2′-pyrrolidin]-2-one, which has shown growth inhibitory activity in breast cancer cells. The present study was aimed to explore the mechanism of anti-tumorigenic action of this newly identified spiro-oxindole compound. Compound G613 inhibited the Mdm2–p53 interaction in breast cancer cells and tumor xenograft. It caused restoration of p53 function by activating its promoter activity, triggering its nuclear accumulation and preventing its ubiquitination and proteasomal degradation. Supportively, molecular docking studies revealed considerable homology in the docking mode of G613 and the known Mdm2 inhibitor Nutlin-3, to p53 binding pocket of Mdm2. The activation of p53 led to upregulation of p53 dependent pro-apoptotic proteins, Bax, Pumaα and Noxa and enhanced interaction of p53 with bcl2 member proteins thus triggering both transcription-dependent and transcription-independent apoptosis, respectively. Additionally, the compound decreased estrogen receptor activity through sequestration of estrogen receptor α by p53 thereby causing a decreased transcriptional activation and expression of proliferation markers. In conclusion, G613 represents a potent small-molecule inhibitor of the Mdm2–p53 interaction and can serve as a promising lead for developing a new class of anti-cancer therapy for breast cancer patients.